Bionics and green technology in maritime shipping: an assessment of the effect of Salvinia air-layer hull coatings for drag and fuel reduction. (24th December 2018) - Busch, J.; Barthlott, W.; Brede, M.; Terlau, W.; Mail, M.
Abstract : To save energy and reduce environmental impacts, new technologies towards a development of a sustainable 'greener' economy are needed. The main opportunity to improve sustainability by reducing emissions is within the transport sector. More than 90% of all goods worldwide are transported by ships. Particularly maritime ships using heavy fuel oil and marine gas oil play a major role. The total fuel consumption of shipping in 2016 was about 250 m t (domestic ca. 50 m t, international shipping ca. 200 m t). The vast portion of the energy consumption of a ship is the need to overcome the drag between ship hull and water—depending on the shape of the vessel and its size up to 90% of total fuel consumption. This means reducing drag helps to save fuel and reduces carbon emissions as well as pollution considerably. Different techniques for drag reduction are known, e.g. the micro-bubble technique or the bulbous bow. We investigated a novel bioinspired technique since 2002: the application of biomimetic surfaces with long-term stable air layers on ship hulls, serving as a slip agent. This technology is based on the Salvinia Effect, allowing a permanent stabilization of air layers under water. In this case study, we analysed the possible savings, which also could be combined with modified micro-bubble technologies. We calculated, based on a selection of five ship types, representing 75% of the world fleet, that air-layer hull coatings could lead to estimated savings of 32.5 million tons of fuel (meaning 13.0% of the worldwide shipping fuel consumption), equal to 18.5 billion US$ and 130.0 million tons of CO2e per year. The positive impacts on global temperature and other greenhouse gases are calculated and could be a contributing factor in accomplishing the UN Sustainable Development Goals and the Paris Agreement to the UN Framework Convention on Climate Change. The study is a contribution to enhance our patchy knowledge concerning the potential economic and ecological benefit of bionics and biomimetic technologies. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology'.